Effects of Migration on Infant and Maternal Health in China. (October 2019) - Tang, Di; Gao, Xiangdong; Rebeira, Mayvis; Coyte, Peter C.
We assess the association between maternal migrant status and health outcomes in China, which has one of the world's largest migrant populations. Health records from the Shanghai First Maternity and Infant Hospital from January 1, 2013, to June 30, 2017, were used to analyze 104 681 live births for Shanghai native-born and migrant women based on International Classification of Diseases, Tenth Revision diagnosis codes and demographic data. Regression analysis including propensity score matching was conducted to investigate the association between maternal migrant status and adverse infant birth outcomes (fetal disease, congenital malformation, neonatal disease) and maternal health after controlling for pregnancy status and socioeconomic factors. The results demonstrate that migrant women had statistically significant increased odds (9.1%-10%, P < .001) of having infants with adverse health outcomes compared with their urban counterparts and that migrant mothers have less likelihood of pregnancy complications and gestational diabetes mellitus. Our results show the mixed effects of migration on infant and maternal health may be a possible outcome of China's Hukou system that often represents an important barrier in accessing prenatal health care by migrant women. Current reforms that improve access to prenatal health care services for migrant women may enhance the health outcomes of their infants.